Cholinesterases as environmental biomarkers to address the putative effects of low, realistic levels of waterborne uranium. (December 2018) - Nunes, B.; Castro, B.B.; Gomes, J.; Carvalho, T.; Gonçalves, F.
Highlights: Exposure to metals is often associated to cholinesterasic (ChE) inhibition. ChE inhibition is a common criteria to assess effects of varied contaminants, e.g. metals. Uranium exposure did not result in ChE inhibition in any tested species. ChE inhibition seems not to be suitable to diagnose uranium exposure. Abstract: To address the issue of potential cholinergic neurotoxic effects in exposed biota, including sentinel or indicator species, a biomarker approach using cholinesterase (ChE) inhibition as effect criterion has been proposed. Waterborne metals and complex metallic effluents (e.g. from mining) also seem to affect ChE activity of numerous aquatic species, although there is debate on the likelihood of this effect. Considering that environmental exposure to mine effluents is a complex phenomenon, complicated by other factors (such as pH), we intended to simulate a uranium rich effluent, to which test organisms were acutely exposed. The objective of the present study was to quantify the effects of waterborne uranium on ChE activity of the freshwater organisms Daphnia magna (crustacean), Corbicula fluminea (mollusc), and Carassius auratus (fish), in order to evaluate the feasibility of using this biomarker to diagnose chemical stress induced by waterborne uranium, resulting from mining activities. The obtained data showed that, despite the large body of evidence pointing to inhibitory effects on cholinesterases caused by metals, uranium was not causative of significant ChE impairment in vivo for any tested organism, at concentrations that represent a worst-case contamination scenario. Considering the obtained results, cholinesterase inhibition is not suited to be integrated into a battery of biomarkers to diagnose uranium exposure. Although our study is strictly laboratorial, it has implications in the use and interpretation of this environmental biomarker in biomonitoring studies, especially of uranium-impacted areas.